Marine oil source of the Yingmaili Oilfield in the Tarim Basin. (December 2015) - Li, Sumei; Pang, Xiongqi; Zhang, Baoshou; Sun, Hao; Sun, Aiyan
Abstract: Although a large amount of petroleum has been discovered in the Tarim Basin, the origin of the oils is still disputed. Yingmaili Oilfield was selected as a case study to further examine hydrocarbon generation and accumulation in the basin. Detailed geochemical studies were conducted to unravel the formation mechanisms. The oils in the field correlate well with Middle–Upper Ordovician (O2+3 ) rocks (or similar rocks). Oil–oil and oil–source rock correlation by maturity parameters of saturate and aromatic hydrocarbons suggest that the Yingmaili and adjacent oils are primarily comparable to source rocks deeper than 6000 m. The results also showed that carbonates might be important potential source rocks as indicated by a relatively high abundance of aromatic sulfur compounds and relatively high C29 /C30 -hopane and C35 /C34 -hopane ratios of the oils, which are typical features of carbonate source rocks. We suggest the oil from wells YG2 and YG2-1C are more suitable to be end members from the O2+3 source rocks (or similar rocks) than the oil from well YM2 as previously suggested. We also suggest that the previous model of hydrocarbon migration along the Ordovician unconformity should be revised. Highlights: The Yingmaili oils were primarily derived from O2+3 and/or similar rocks. Most oils were sourced from potential source rocks >6000 m. Carbonate rocks are potential source rocks while mudstone/shale was main source rock recognized. YG2 and YG2-1C were suggested to be end member oils from O2+3 and/or similar rocks.